(untitled) (Research, Society and Development, 2021)
The SARS-CoV-2 infection started in December 2019 in Wuhan province, China, and spreads worldwide in 2020. Coronavirus belongs to the Coronaviridae family and causes a respiratory disease called Covid-19. The entire humanity was strongly impacted in the face of an unexpected and rapidly expanding pandemic to Covid-19 that surprised everyone, especially health professionals, in coping with this overwhelming illness, making it necessary to consider moral norms to be observed, such as the sense of responsibility. The study is a narrative review whose general objective is to describe the changes that occurred in pharmaceutical legislation during the Covid-19 pandemic. The specific objectives are to describe what the rules were like before the pandemic was established, describe the changes that occurred and learn about the implications for the pharmacist in his performance. With the Coronavirus pandemic, there were many changes in legislation to reduce viral spread by decreasing social contact and in relation to pharmacological treatment, modifying prescriptions and updating the lists of controlled drugs. In this way, the importance of the pharmaceutical professional is perceived in terms of controlling the spread of the virus and caring for patients with the disease.